Passive solutions to reduce the need for cooling in buildings - Wei Feng (Asian Development Bank Institute (ADBI), 2023)
This paper introduces designs, technologies, and best practices aimed at reducing the cooling energy demand in buildings. It covers the basic principles of why occupants need cooling to meet thermal comfort requirements and how heat is transferred into buildings from the outdoor environment. Passive designs help buildings make use of natural cooling resources and maximize free cooling opportunities such as natural ventilation. The paper summarizes best practices for each passive strategy used in buildings. As a result, architects and engineers will also be able to better orient functional spaces and design cooling operation strategies to provide cooling for spaces where and when needed. The building envelope provides the necessary insulation to stop heat transfer from a hot outdoor environment to an indoor one. Criteria for designing a high-performance building envelope are introduced. For fenestration systems, this paper covers energy-efficient technologies for glazing and shades to reduce solar heat gain. Cool roofs can effectively reflect sunlight back to the atmosphere and also significantly reduce buildings' solar heat gain. Also, to create a cooler outdoor environment in cities, strategies are introduced to mitigate the urban heat island effect. Finally, policy recommendations are suggested, such as improving building codes and standards; creating labels and certifications for passive cooling technologies; establishing incentive programs to promote passive green buildings; educating architects, builders, and occupants; and developing sustainable city policies.
Keywords: R0; 330; buildings; building envelope; cool roofs; thermal comfort; passive cooling; policies